Surgery Technique, Gender, Age on Hirschsprung Assosiated Enterocolitis Score of Post-Pull through Hirschprung Patients - Haikal Effendi; Jon Efendi; Budi Pratama Arnofyan (International Journal Labs, 2022)
Knowing if there are differences in HAEC scores following pull-through procedures between groups due to the interaction of surgical techniques with gender by controlling the influence of patient age is as important as determining if there are differences in Pull-Through through the procedure between male and female patients. The purpose of this study was to compare haec score profiles after Pull-Through surgery using Duhamel's surgery technique and TEPT surgery technique to see whether there was a difference through the process of comparing HAEC scores after the Pull between Duhamel's surgical technique and TEPT surgery technique while controlling the patient's age impact. The study, which compares Duhamel's method with the TEPT process, is an ex-post facto descriptive and inferential study with the aim of determining the profile and variation of post-pull-through HAEC scores. Patients at RSUP Dr. M. Djamil Padang who suffered from Hirschsprung disease between 2018 and 2022 were the study population. All patients in the study sample, compiled using the method of complete sampling, were between 0 and 5 years old. The HAEC scores of individuals with Hirschsprung's disease are determined by a combination of age, gender, and surgical approach. HAEC scores are strongly influenced by age variables alone, the older the patient, the higher the HAEC score. There was a difference in the average HAEC score between the group of patients undergoing Duhamel surgery and the group undergoing TEPT surgery, with the HAEC score of the Duhamel engineering group being higher than that of the TEPT surgery technique group. The average HAEC score for the male and female patient groups was the same.